APPLYING INTERNATIONAL HUMANITARIAN LAW TO CYBER-ATTACKS - Dan-Iulian VOITAŞEC (Challenges of the Knowledge Society)
Technology plays an important role in everyday life. Technological advancement can be found in every field of government including the military. Because of this, new means and methods of conducting hostilities have emerged. Cyber warfare starts to represent the latest challenge at an international level. States and non-state actors have started to implement new security policies and new defences against cyber-attacks but also have embraced using cyber-attacks as a method of conducting hostilities. The question that has to be answered regarding the use of cyber-attacks is what is the legal regime that governs such attacks and if IHL can apply to cyber warfare?